2019
DOI: 10.1177/0021886319832013
|View full text |Cite
|
Sign up to set email alerts
|

Affective Information Processing in Self-Managing Teams: The Role of Emotional Intelligence

Abstract: Based on a multilevel data set collected from 599 individuals working in 102 self-managing teams, we examined the relationship between emotional intelligence (EI) and team member performance, focusing on the dimensions of teamwork and leadership performance. Furthermore, we explored the moderating role of team-level characteristics, such as noninformational diversity, size, and collective EI on the EI–performance relationship. As predicted, team members with higher EI were better at facilitating teamwork and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 122 publications
(167 reference statements)
1
16
0
Order By: Relevance
“…However, the effect disappeared in the case of high team average emotional intelligence. Applying the same questionnaire as Paik et al (2019), Rozell and Scroggins (2010) found that the understanding of emotions was related to negative feelings regarding group member relationships and group cohesion, both being dimensions of group satisfaction. The authors explained this phenomenon stating that this is because a better understanding of the team colleagues' emotions allows the perception of tensions that other colleagues could not even sense.…”
Section: Supporting and Cooperatingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the effect disappeared in the case of high team average emotional intelligence. Applying the same questionnaire as Paik et al (2019), Rozell and Scroggins (2010) found that the understanding of emotions was related to negative feelings regarding group member relationships and group cohesion, both being dimensions of group satisfaction. The authors explained this phenomenon stating that this is because a better understanding of the team colleagues' emotions allows the perception of tensions that other colleagues could not even sense.…”
Section: Supporting and Cooperatingmentioning
confidence: 99%
“…The relevance of characteristics that only one team member displayed was the subject of only a few studies. Paik et al (2019) showed that individual emotional intelligence was especially effective when the team average emotional intelligence was low. Similarly, the assertiveness of the team members holding critical roles was predictive of high team performance and satisfaction (Pearsall & Ellis, 2006).…”
Section: The Interplay Of Team Members' Ksaos Within Smtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, although research on whether team EI contributes to more effective team functioning and outcomes has increased recently (e.g., Jamshed & Majeed, 2019; Macht et al, 2019; Paik et al, 2019), how and when team-based EI affects team performance has been rarely examined (for one exception, see Wang, 2015). We traced mean levels of team member EI to task performance and examined the effects of team EI on team effectiveness through the structural influence of team process which is moderated in part by the shared perceptions of team processes.…”
mentioning
confidence: 99%
“…The role and impact of emotional intelligence on performance has been studied also at team level. A brand new study (Paik;Seo, and Jin, 2019) found out that team members with higher EI were better at facilitating teamwork and playing the role of informal leaders than those with lower EI. The positive contribution on team performance was stronger for teams with greater diversity, larger sizes, and with lower average levels of team member EI.…”
Section: Emotional Intelligence Leadership and Performancementioning
confidence: 99%